Beta convergence analysis of gross value added in the high-technology manufacturing industries - Șerban, Andreea Claudia; Pelinescu, Elena; Dospinescu, Andrei Silviu (Technological and Economic Development of Economy, 2022)
The paper examines the recent developments in the high-technology manufacturing sectors in the EU28 countries, focusing on the β-convergence of gross value added in the Manufacture of computers, electronic, and optical products, and the Manufacture of basic pharmaceutical products and pharmaceutical preparations. We employ two dynamic panel models estimated using the system of generalized method of moments (GMM) to address the risk of an endogeneity bias. The panel data analysis indicates a higher convergence for the Manufacture of computer, electronic, and optical products at 16.4% compared to 2.2% for the Manufacture of basic pharmaceutical products and pharmaceutical preparations, which is consistent with the existence of fewer barriers and higher exposure to competition in the case of the first analyzed sector. In the context of the role of the high-technology manufacturing industries as an engine of growth and the existing performance differences between the EU28 countries in terms of gross value added in the analyzed sectors, we investigated the β-convergence for two groupings EU15 and the new EU member states. We found that the new EU member states display a higher β-convergence rate than EU15, but also that they have a lower capital intensity. The result highlights the potential risk of some of the new EU member states becoming laggers in terms of the underlying factors behind gross value added as investment and labour force. First published online 06 December 2021